The breaking beads approach for photocleavage from solid support. Issue 22 (22nd May 2020) - Bakhatan, Yasmeen; Alshanski, Israel; Grunhaus, Dana; Hurevich, Mattan
Abstract : Grinding of polystyrene beads accelerates photocleavage. Abstract : Photocleavage from polystyrene beads is a pivotal reaction for solid phase synthesis that relies on photolabile linkers. Photocleavage from intact porous polystyrene beads is not optimal because light cannot penetrate into the beads and the surface area exposed to irradiation is limited. Thus, hazardous, technically challenging and expensive setups are used for photocleavage from intact beads. We developed a new concept in which grinding the beads during or prior to irradiation is employed as an essential part of the photocleavage process. By grinding the beads we are exposing more surface area to the light source, hence, photocleavage can be performed even using a simple benchtop LED setup. This approach proved very efficient for photocleavage of various model compounds including fully protected oligosaccharides.